Associations of particulate matter with atopic dermatitis and chronic inflammatory skin diseases in South Korea. (1st February 2022) - Park, T. H.; Park, S.; Cho, M. K.; Kim, S.
Summary: Background Particulate matter (PM) is a mixture of solid and liquid particles suspended in air, which originates from industrial plants or vehicle emissions. Although the skin is the primary body area of contact with air pollutants, the associations between PM and chronic inflammatory skin diseases has not been well established. Aim To investigate associations between PM and atopic dermatitis (AD) and between PM and other chronic inflammatory dermatoses, using data from the Korean Health Insurance Review and Assessment Service. Methods Monthly disease statistics from the seven largest cities in South Korea (Seoul, Busan, Daegu, Incheon, Gwangju, Daejeon, Ulsan) and from Jeju Island (in total, a population of 23 288 000 for all eight areas) were included. Based on daily air pollution level and weather forecast from 2015 to 2019, multivariate negative binomial regression analysis was conducted to estimate monthly visits of AD with respect to outdoor air pollutants: coarse PM with a diameter of ≤ 10 μm (PM10) and fine PM with a diameter of ≤ 2.5 μm (PM2.5) ozone (O3 ), nitrogen dioxide (NO2 ), sulphur dioxide (SO2 ) and carbon monoxide (CO). Results Increases in the levels of PM2.5, PM10, SO2 and CO were associated with significant increases in monthly patient visits for AD. Every 10 μg/m 3 increase in PM2.5 and PM10 resulted in patient visit increases of 2.71% (95% CI 0.76–4.71; P < 0.01) and 2.01% (95% CI 0.92–3.11, P < 0.001), respectively, while every 1 part per billion (ppb) increase in SO2 and every 100 ppb increase in CO resulted in visit increases of 2.26% (95% CI 1.35–3.17; P < 0.001) and 2.86% (95% CI 1.35–4.40; P < 0.001), respectively. O3 and NO2 were not associated with increased patient visits for AD. Increases in PM2.5 and PM10 concentrations were also significantly associated with increases in patient visits for psoriasis, seborrhoeic dermatitis and rosacea. Conclusion Our data suggest that PM is associated with AD and other chronic inflammatory skin diseases. Abstract : Particulate matter (PM) was associated with atopic dermatitis (AD). Fine PM (diameter of ≤ 2.5 μm) had a greater impact on AD than coarse PM (diameter of ≤ 10 μm) did. Nitrogen dioxide, sulphur dioxide (SO2 ), ozone and carbon monoxide (CO) were also assessed, with SO2 and CO found to be associated with increased clinic visits of patients with AD. PM was also associated with inflammatory skin diseases including psoriasis, seborrhoeic dermatitis and rosacea, whereas tinea was not associated with PM.